2018
DOI: 10.28945/4137
|View full text |Cite
|
Sign up to set email alerts
|

Ladies First: The Influence of Mobile Dating Applications on the Psychological Empowerment of Female Users

Abstract: Aim/Purpose: This study was undertaken to shed light on how the use of a heteronormative mobile dating application creates an environment to promote psychological empowerment among female users within the online dating scene. The study focused on a mobile dating application which specifically challenges traditional gender roles, namely Bumble. Background: Mobile dating applications have become an increasingly popular medium for people to meet potential partners. However, users’ pre-existing social norms and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…This is in line with Guerrero et al (2018) who stated that flirting is not necessarily related to a romantic relationship or sex. Researchers found that being the target of a flirt can be perceived as flattery and interest in the own person, which, consequently, can be associated with positive emotions and a confidence boost, even in a computer-mediated setting ( Hall, 1993 ; Cialdini, 2009 ; Tanner and Tabo, 2018 ). It is likely that this boost of confidence is associated with the fact that flirting also represents a sign of genuine interest in another person ( Hall et al, 2010 ).…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…This is in line with Guerrero et al (2018) who stated that flirting is not necessarily related to a romantic relationship or sex. Researchers found that being the target of a flirt can be perceived as flattery and interest in the own person, which, consequently, can be associated with positive emotions and a confidence boost, even in a computer-mediated setting ( Hall, 1993 ; Cialdini, 2009 ; Tanner and Tabo, 2018 ). It is likely that this boost of confidence is associated with the fact that flirting also represents a sign of genuine interest in another person ( Hall et al, 2010 ).…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…"When members of the opposite sex match on Bumble, women are required to make the first move, shifting old-fashioned power dynamics and encouraging equality from the start" (Bumble, 2020). In line with Bumble's ambition to empower women, previous research revealed that some women make a conscious choice to use Bumble because of its general reputation for female empowerment (Pruchniewska, 2020;Tanner & Tabo, 2018) but did not focus on the interplay of technological affordances and empowerment. In addition, mobile research suggests that empowerment through technology can inadvertently bring about forms of disempowerment as well (Donner, 2015).…”
Section: Technological Affordances Of Mobile Dating Appsmentioning
confidence: 99%
“…This study builds on previous work on female mobile dating app use (e.g., Chan, 2018;MacLeod & McArthur, 2019;Tanner & Tabo, 2018), especially by Bivens and Hoque (2018), who used a material-semiotic analysis approach to analyze Bumbles software, self-advertisement, and media coverage regarding its meaning-making of gender, sex, and sexuality with a special focus on how Bumble perpetuates aggressive masculinity, cisgender White women's sexuality, safety, and control in its narrative. In line with this, Pruchniewska (2020) contributes to the women being at risk debate (e.g., Duguay et al, 2020;Hess & Flores, 2018) through empirical insights gained by interviews with female Bumble users revealing particular strategies of women to avoid harassment and safe mobile dating app navigation.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between Bumble and other apps is that after two partners swipe right on each other and “match” on the app, only a woman can initiate messaging. This feature was created with the intent to empower women and reduce the likelihood of online harassment initiated by men (Pruchniewska, 2020; Stratmoen et al, 2020; Tanner & Tabo, 2018). While research has indicated that women do feel empowered using the app to choose or reject matches (Pruchniewska, 2020; Tanner & Tabo, 2018), little is known about how female users reject others and communicate on the app.…”
mentioning
confidence: 99%
“…This feature was created with the intent to empower women and reduce the likelihood of online harassment initiated by men (Pruchniewska, 2020; Stratmoen et al, 2020; Tanner & Tabo, 2018). While research has indicated that women do feel empowered using the app to choose or reject matches (Pruchniewska, 2020; Tanner & Tabo, 2018), little is known about how female users reject others and communicate on the app. Thus, this study fills a gap in the literature by investigating which strategies women most commonly use to reject partners on Bumble.…”
mentioning
confidence: 99%